2017
DOI: 10.1111/jeu.12399
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Genetic Characteristics of Cryptosporidium hominis and Cryptosporidium andersoni in Horses from Southwestern China

Abstract: A total of 333 fecal specimens from horses in southwestern China were genotyped based on analysis of the small subunit rRNA (SSU rRNA) gene. Cryptosporidium hominis and Cryptosporidium andersoni were identified in 2 and 4 stool specimens, respectively. The identification of C. hominis was confirmed by sequence analysis of the 70‐kDa heat shock protein (HSP70) and oocyst wall protein (COWP) genes. Subtyping analysis of the 60‐kDa glycoprotein (GP60) gene sequence of C. hominis revealed a new rare subtype Id, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 34 publications
5
17
0
Order By: Relevance
“…C. andersoni is actually the most common Cryptosporidium species responsible for cattle cryptosporidiosis in yearlings and adults. Recently, with the establishment of the multilocus sequence typing (MLST) tool used for subtyping C. andersoni [74], the MLST subtypes and population genetic structure of C. andersoni from animals have been analyzed, including those from cattle, sheep, horses, golden takins, monkeys, camels, ostriches, and hamsters [75][76][77][78][79][80][81][82][83][84]. These MLST data of animal-derived C. andersoni isolates will be helpful in the future for source attribution of infection/contamination of C. andersoni and to understand its transmission dynamics in humans.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…C. andersoni is actually the most common Cryptosporidium species responsible for cattle cryptosporidiosis in yearlings and adults. Recently, with the establishment of the multilocus sequence typing (MLST) tool used for subtyping C. andersoni [74], the MLST subtypes and population genetic structure of C. andersoni from animals have been analyzed, including those from cattle, sheep, horses, golden takins, monkeys, camels, ostriches, and hamsters [75][76][77][78][79][80][81][82][83][84]. These MLST data of animal-derived C. andersoni isolates will be helpful in the future for source attribution of infection/contamination of C. andersoni and to understand its transmission dynamics in humans.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…This was substantiated recently by multilocus sequence type (MLST) analysis of C. ubiquitum isolates (Tang et al, 2016 ). An MLST tool has also been developed for C. andersoni and C. muris (Feng et al, 2011a ), and used by Chinese scientists in population genetic characterizations of gastric Cryptosporidium species in various areas (Wang et al, 2012 ; Zhao et al, 2013 , 2014 ; Du et al, 2015 ; Zhao G. H. et al, 2015 ; Qi et al, 2016 ; Deng et al, 2017 ). It was shown that while the population structure of C. andersoni was clonal in Shaanxi and Heilongjiang provinces (Zhao et al, 2013 , 2014 ), it was epidemic in Xinjiang and other regions (Wang et al, 2012 ; Qi et al, 2016 ).…”
Section: Molecular Epidemiologic Toolsmentioning
confidence: 99%
“…is a recent development in China (Chen and Huang, 2007 ; Wang et al, 2008a , b , c ), genotyping and subtyping tools are now widely used in the characterization of Cryptosporidium spp. in various animals (Karim et al, 2014 ; Liu et al, 2014a , b , 2015a , b ; Ma et al, 2014 , 2015 ; Qi et al, 2014 , 2015a , b , d , 2016 ; Wang L. et al, 2014 ; Ye et al, 2014 ; Zhao et al, 2014 ; Du et al, 2015 ; Li J. et al, 2015 , 2017 ; Liu A. et al, 2015 ; Li W. et al, 2015 , 2017 ; Qi, M. Z., et al, 2015 ; Wang et al, 2015a , b ; Zhang et al, 2015a , b ; Zhao G. H. et al, 2015 ; Zhao Z. et al, 2015 ; Jian et al, 2016 ; Li F. et al, 2016 ; Li P. et al, 2016 ; Li Q. et al, 2016 ; Peng et al, 2016 ; Taylan-Ozkan et al, 2016 ; Xu et al, 2016 ; Yang et al, 2016 ; Zhang S. et al, 2016 ; Deng et al, 2017 ; Gong et al, 2017 ; Zou et al, 2017 ). The use of molecular diagnostic tools in prevalence studies has led to the identification of significant differences in the transmission of Cryptosporidium spp.…”
Section: Molecular Epidemiologic Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although C. andersoni is widely considered a cattlespecific Cryptosporidium species, it's occurrence in other animals and humans is increasing [18,19]. To date, C. andersoni has been detected in cattle, yaks, sheep, goats, deer, rodents, houses, non-human primates, camels, and giant pandas [18,[20][21][22][23][24][25][26][27][28][29]. Contrasting with its occasional detection in other animals, C. andersoni is the common Cryptosporidium species in cattle, which appear its natural host [18].…”
Section: Discussionmentioning
confidence: 99%